Mitigation of Heavy Metal Contamination in Soil via Successive Pig Slurry Application. Issue 7 (17th November 2017) - Furtado e Silva, João Antônio Montibeller; Brasil do Amaral Sobrinho, Nelson Moura; García, Andrés Calderín; Pandolfo, Carla Maria; da Veiga, Milton
ABSTRACT: This study evaluates heavy metal removal associated with phytomass management in a Typic Hapludox after three applications of pig slurry. Like humic acids in pig slurry were characterized through physics and chemical spectroscopy technics. Heavy metal levels were determined in ration that was offered to pigs, anaerobically digested pig slurry, and plant tissues from pig slurry-fertilized black oat ( Avena strigosa Schreb.) and ryegrass ( Lolium multiflorum Lam.) intercrop. Soil contamination was evaluated by the pseudo-total heavy metal levels in six soil layers and the bioavailable levels in the top soil layer. Results indicate that the ration is the origin of heavy metals in the pig slurry. The approximate levels in the ration were as follows (mg kg −1 ): Cu 23.9, Zn 92.02, 153.15, Mn 30.98, Ni 0.23, Pb 10.75, Cr 0.34, Co 0.08, and Cd 0.05. The approximate levels of these metals in the pig slurry were as follows (mg kg −1 ): Cu 71.08, Zn 345.67, Fe 83.02, Mn 81.71, Ni 1.13, Pb 4.35, Co 0.28, and Cd 0.16. Like humic acids contained 55% aliphatic chains, 14% oxygenated aliphatic chains, and 15% carboxyls, demonstrating their high capacity for interaction with heavy metals by forming soluble complexes. Soil contamination was indicated by the accumulation of heavy metals in the six soil layers in relation to the applied pig slurry dose (ranged as follows (mg kg −1 ): Cu 110 to 150, Zn 50 to 120, Ni 20 to 40, and Pb 12 to 16) and as bioavailable forms (levels ranged as follows (mg kg −1 ): Cu < 1, Zn 1.0–1.5, Ni 0.1–1.5, and Pb 1.9–6.3). The positive correlation between heavy metal accumulation in the plants and soil bioavailable heavy metal levels and the lowest heavy metal levels under higher intensity of phytomass removal demonstrate the ability of phytomass management to reduce soil contamination.